On Rewards and Benefits for Noble Clients and Agents. Guillermo Verdugo in the Service of Franz von Dietrichstein (Theatrum historiae, 2020)
The aim of the article is to introduce the activities of the Spanish nobleman Guillermo Verdugo in the service of the Bishop of Olomouc and Cardinal Franz von Dietrichstein. Based on the analysis of the correspondence of Guillermo Verdugo deposited in the Moravian Provincial Archive in Brno, this research mainly focuses in the context of current research of the patronage and clientelism on the topic of rewards and benefits that Guillermo Verdugo received for his services.
Keywords: Guillermo Verdugo; Franz von Dietrichstein; reward; patron-client ties; clientelism